William Shirley papers - Shirley, William, 1694-1771.
Orders (1746, 1755) issued by Shirley as commander of British colonial forces to John Stoddard and Thomas Dunbar; notice (1756) signed by Shirley of the promotion of Jonathan Shaw to the position of captain-general; expense account (1748) for an expedition to Canada; and muster list (1744-1755) of colonial military companies.
In part, positive photocopy.
British army officer and colonial governor of Massachusetts.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Dunbar, Thomas, -- -1767.; Shaw, Jonathan, -- active 1756.; Stoddard, John, -- 1681-1748.; Canada -- History -- To 1763 (New France); Great Britain. -- Army -- Colonial forces -- America; Great Britain -- Colonies -- America; Massachusetts -- Politics and government -- To 1775.; United States -- History -- Colonial period, ca. 1600-1775.; United States -- History -- French and Indian War, 1754-1763.; Army officers, British; Governors -- Massachusetts